AN ANALYSIS OF TEACHER’S FEEDBACK ON STUDENTS’ WRITING TASK - D Darmanto; Fetty Yulia Utari; Abdul Rahim (Jurnal Ilmiah Global Education, 2023)
The use of feedback is strongly crucial in learning of English as a second or foreign language. It is crucial because it can motivate and support the students in learning English. This study focused on analyzing and describing the teacher’s feedbacks used on students’ writing tasks and students’ perspective about it. In this research, case study was applied as research method. The subject of this research was the tenth graders of MAN 2 Sumbawa in school year 2021-2022. In collecting the data, the researchers used several instruments such as the students’ writing tasks, semi structure interview guide and observation sheet to gain the data from the respondents. All of the data were analyzed to know the type of teacher’s feedbacks and students’ responses on it. The findings of this research showed that there were two types of feedback given by the teacher, namely written and oral feedback. Both of those feedbacks were implemented in the students’ writing task. The finding also showed the use of feedback in English as foreign language (EFL) context was great significance to stimulate the students to make good writing. EFL students who involved in this study had expressed their strong belief in its importance and applicability. They gave positive responses to the use of written and oral feedback. Most of the students stated that the teacher’s feedback was a good motivation in learning and believed that the teacher’s feedback helped them in improving their writing proficiency.